How Do Students Want to Learn in Online Distance Education? Profiling Student Preferences - Rob Koper (International Review of Research in Open and Distributed Learning, 2015)
How do (potential) students differ in their preferences for the organization of online and distance courses and programs, can these differences be grouped into preference profiles, and are there any associations between these profiles and variables, such as achievement and dropout, that are relevant for the promotion and design of online and distance teaching?